Managing social media platforms in Cross-border E-Commerce: The Case of China B2C Sellers - Bai, Shikun (2018)
Cross-border e-commerce is a new type of international business based on the support of internet. In recent 10 years, China has witnessed the rapid development of this industry. The development growth rate of Business-to-Customer (B2C) is predicted to be substantial. The huge potential of China’s B2C cross-border e-commerce market is attracting a large number of sellers. Since China’s cross-border e-commerce B2C sales network spreads all over the world, it is meaningful for Chinese sellers to use social media platforms for better communication with overseas customers, which in turn achieves sales promotion. Social media platforms such as Facebook, LinkedIn and Pinterest enable to improve the operation efficiency of China’s B2C sellers, and the usage process of social media platform is worth investigating. To guide and inspire China’s cross-border e-commerce sellers to use social media platforms, this dissertation divides the exploratory process into three parts. Firstly, this dissertation will review the history of China’s cross-border e-commerce development and the usage of social media platforms in business. Next, four in-depth interviews of professional China’s cross-border e-commerce B2C sellers (in two different firms) are used to explore the different usage of social media platforms at different development stages. At last, the focus of China’s cross-border e-commerce B2C sellers using social media platforms will be highlighted.